Współpraca w doświadczeniach studentów = Experience in cooperation of Univeristy of Zielona Góra students - Bąbka, Jarosław; Binnebesel, Józef (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article presents a part of the research and diagnostic testing results concerning the experiences of University of Zielona Góra students associated with cooperation (profitability of cooperation and competition at present, roles most often performed while working in group, positive and negative experiences gathered by the students while working in a group, evaluation of cooperation skills).
Keywords: Uniwersytet Zielonogórski; studenci; współpraca